Proximal hypospadias repair using the koyanagi-hayashi technique. A review of 15 cases - Mouafo Tambo Faustin; A S Nwaha Makon; C Kamadjou; G Fossi; O G Andze; M A Sosso; P Y Mure (Wolters Kluwer Medknow Publications, 2018)
Background: Several surgical approaches or modifications of existing techniques have been described for the repair of hypospadias. In Sub-Saharan Africa, a two-stage approach is the preferred option in proximal cases with severe penile curvature. Objective: The authors describe their experience with one-stage repair of proximal hypospadias with severe penile curvature using the Koyanagi-Hayashi technique. Methodology: Three hundred and ten patients were seen at the outpatient clinic from November 2009 to November 2015. All patients aged between 2 and 17 years with a confirmed diagnosis of proximal hypospadias and operated according to the Koyanagi-Hashashi technique were included in the study. Results: The mean age at diagnosis was 6.7 ± 4.35 years (81 months). The level of the hypospadias was penile in 60%, scrotal 33.5%, and posterior in 6.6% of cases. The most common complications after primary repair were partial breakdown of the urethroplasty (44.8%), urethra-cutaneous fistula (3.3%), dehiscence of the glanuloplasty (22.2%), and recurrent penile curvature (11.1%). Discussion: The high psychological implication of this condition in children and adolescents at the time of diagnosis in our context was a major weakness of our study. However, it turned out to be an advantage as the patients could be involved in the decision-making in as much as the previous gender was taken into consideration. Conclusion: A one-stage repair approach as described by Koyanagi-Hayashi also provides good aesthetic and functional outcome. It thus stands out as an alternative even in our African setting.